Groundwater Vulnerability Assessment Using a GIS-Based Modified DRASTIC Model in Agricultural Areas - Gheisari, Narges (Université d'Ottawa / University of Ottawa, 2017)
DRASTIC model is the most widely used method for aquifer vulnerability mapping which consists of seven hydrogeological parameters. Despite of its popularity, this technique disregards the effect of regional characteristics and there is no specific validation method to demonstrate the accuracy of this method. The main goal of this research was developing an integrated GIS-based DRASTIC model using Depth to water, Net Recharge, Aquifer media, Soil media, Topography, Impact of vadose zone and Hydraulic Conductivity (DRASTIC). In order to obtain a more reliable and accurate assessment, the rates and weights of original DRASTIC were modified using Wilcoxon rank-sum non-parametric statistical test and Single Parameter Sensitivity Analysis (SPSA). The methodology was implemented for the Shahrekord plain in the southwestern region of Iran. Two different sets of measured nitrate concentrations from two monitoring events were used, one for modification and other for validation purposes. Validation nitrate values were compared to the calculated DRASTIC index to assess the efficacy of the DRASTIC model. The validation results obtained from Pearson's correlation and chi-square values, revealed that the modified DRASTIC is more efficient than original DRASTIC. The modified rate/weight DRASTIC (spline) model showed the highest correlation coefficient and chi square value as 0.88 and 72.93, respectively, compared to -0.3 and 25.2 for the original DRASTIC (spline) model. The integrated vulnerability map showed the high risk imposed on the southeastern part of the Shahrekord aquifer. In addition, sensitivity analysis indicated that the removal of net recharge parameter from the modified model caused larger variation in vulnerability index showing that this parameter has more impact on the DRASTIC vulnerability of the aquifer. Moreover, Aquifer media (A), Topography (T) and Impact of vadose zone (I) were found to have less effect and importance compared to other variables as expected. Therefore, reduced modified DRASTIC model was proposed by eliminating A, T and I parameters. Pearson's correlation coefficient and chi-square value for the reduced model were calculated as 0.88 and 100.38, respectively, which was found to be as reliable as full modified DRASTIC model.
Keywords: Vulnerability mapping; DRASTIC; Sensitivity analysis; Shahrekord aquifer